2012
DOI: 10.1177/0890334412447079
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Practices and Breastfeeding Rates before and after the UNICEF/WHO 20-Hour Course for Maternity Staff

Abstract: Training of health professionals, based on the BFHI, was associated with significant improvement in some Baby-Friendly hospital practices and initial exclusive breastfeeding rates. A high rate of in-hospital supplementation may partly explain the lack of improvement in breastfeeding exclusivity and duration after discharge. Strong institutional support and commitment is needed to enable full implementation of recommended Baby-Friendly practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 11 publications
0
67
0
4
Order By: Relevance
“…A national study conducted in Croatia found that ABF rates improved from pre to post BFHI implementation, and ABF rates increased even further after community‐based support groups were introduced as part of the national breastfeeding programme strategy (Bosnjak et al, ). A more recent study conducted in a maternity ward in Croatia that assessed BFHI steps 4 to 9 found that exposing maternity staff to the 20‐h UNICEF/WHO BFHI training led to greater adherence to some steps 4 (early contact), 7 (rooming‐in) and 8 (BF on demand) (Zakarija‐Grkovic et al, ). The intervention increased EBF during the first 48 h after birth but was not associated with longer‐term benefits in breastfeeding outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…A national study conducted in Croatia found that ABF rates improved from pre to post BFHI implementation, and ABF rates increased even further after community‐based support groups were introduced as part of the national breastfeeding programme strategy (Bosnjak et al, ). A more recent study conducted in a maternity ward in Croatia that assessed BFHI steps 4 to 9 found that exposing maternity staff to the 20‐h UNICEF/WHO BFHI training led to greater adherence to some steps 4 (early contact), 7 (rooming‐in) and 8 (BF on demand) (Zakarija‐Grkovic et al, ). The intervention increased EBF during the first 48 h after birth but was not associated with longer‐term benefits in breastfeeding outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst all groups would benefit from an increase in positive attitude towards breastfeeding, bottle-feeding intenders and those with no clear intention might benefit from more intensive attempts to build self-efficacy in relation to breastfeeding (see [49,50]). In line with clinician expectations, we did find a small group of mothers with mixed-feeding intentions (10%), who were more likely to be of Pakistani origin.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses can play a major role in preventing in-hospital supplementation that can impede the lactation process, associated with interruption of breastfeeding [14, 49]. The other significant barrier refers to the unfavorable remarks from the mother's support system with respect to nursing practices based on the BFHI.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses could benefit from the WHO/UNICEF 20-hour training, which seems to increase their self-efficacy in supporting mothers with breastfeeding [50]. This training is also known to foster a better compliance with the BFHI among nurses [1, 14, 17, 19, 50, 53], among organizations [19] and partners involved in the provision of care in the antenatal period [1]. Nonetheless, not all nurses adopt the BFHI, even with this training [20, 57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation